The effect of impurity-induced lattice strain and Fermi level position on low temperature oxygen diffusion in silicon - Zeng, Z; Murphy, J; Falster, R; Ma, X; Yang, D; Wilshaw, P (2011)
Oxygen diffusion in silicon is known to be affected by high concentrations of impurities, although the mechanism underpinning this is poorly understood. We have studied oxygen transport in Czochralski silicon by analyzing data on the locking of dislocations by oxygen as a function of time and temperature. In this paper, we present new data from crystals grown to contain high levels of germanium and arsenic. We analyze these new data, together with our previous data for silicon with a high boron concentration, to further the understanding of the mechanism by which high impurity concentrations affect oxygen transport at temperatures at which the oxygen dimer dominates transport (up to 550° C). Our results show that a high level of boron doping (∼3 × 10 18cm-3) enhances the effective diffusivity of oxygen by a factor of ∼8 to ∼25 relative to low doped material with the same oxygen concentration. High levels of germanium doping (∼8 × 10 19cm-3) and arsenic doping (∼2 × 10 19cm-3) can both have a slight retardation effect on oxygen transport. The magnitude of the reduction measured is less than a factor of ∼4 in the heavily germanium doped specimens and less than a factor of ∼5 in the heavily arsenic doped specimens, and in most cases is significantly less than this. Germanium doping introduces considerable strain into the silicon lattice without affecting the Fermi level position, so data from these samples show that lattice strain affects oxygen dimer transport. The arsenic and boron doping levels in the materials studied give rise to lattice strain with a smaller magnitude and opposite sign to that in the germanium doped samples. It is therefore suggested that the Fermi level position also affects the transport of oxygen dimers. © 2011 American Institute of Physics.